2007
DOI: 10.1136/oem.2007.033175
|View full text |Cite
|
Sign up to set email alerts
|

Temperature, temperature extremes, and mortality: a study of acclimatisation and effect modification in 50 US cities

Abstract: Objectives: The authors examined the increase in mortality associated with hot and cold temperature in different locations, the determinants of the variability in effect estimates, and its implications for adaptation. Methods: The authors conducted a case-crossover study in 50 US cities. They used daily mortality and weather data for 6 513 330 deaths occurring during 1989-2000. Exposure was assessed using two approaches. First, the authors determined exposure to extreme temperatures using city-specific indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
361
4
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 461 publications
(404 citation statements)
references
References 42 publications
30
361
4
9
Order By: Relevance
“…This study specifically addresses mortality associated with extremely hot and cold days. By isolating the effect of single days of extreme cold temperatures the study results should not be affected by confounding factors related to generally higher wintertime mortality rates such as increased respiratory infections and cardiovascular disease (Medina-Ramon and Schwartz 2007;Mercer 2003). Several recent literature reviews suggest that the factors leading to these higher wintertime mortality rates are unlikely to be sensitive to climate warming (Ebi and Mills 2013;Kinney et al 2012), and therefore the changes in cold mortality identified by this study are likely to compose the majority of the changes in winter-time deaths resulting from warming.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study specifically addresses mortality associated with extremely hot and cold days. By isolating the effect of single days of extreme cold temperatures the study results should not be affected by confounding factors related to generally higher wintertime mortality rates such as increased respiratory infections and cardiovascular disease (Medina-Ramon and Schwartz 2007;Mercer 2003). Several recent literature reviews suggest that the factors leading to these higher wintertime mortality rates are unlikely to be sensitive to climate warming (Ebi and Mills 2013;Kinney et al 2012), and therefore the changes in cold mortality identified by this study are likely to compose the majority of the changes in winter-time deaths resulting from warming.…”
Section: Discussionmentioning
confidence: 99%
“…We incorporate the criteria for extremely hot and cold days and the city-specific mortality results from Medina-Ramon and Schwartz (2007). Specifically, Medina-Ramon and Schwartz (2007) calculated the daily mortality impact for combinations of extremely cold and hot days in 50 cities using local mortality and weather data from 1989 to 2000.…”
Section: Daily Mortality Response To Extreme Temperaturesmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a growing consensus that global climate change will adversely affect human health as the intensity and frequency of heat waves and high air pollution episodes are projected to increase under future climate scenarios, (e.g., Last and Chiotti 2001;Riedel 2004;Meehl and Tebaldi 2004;Medina-Ramón and Schwartz 2007). As IPCC (2007) pointed out, increased heat waves could increase risks of human mortality and morbidity, with very likely likelihood of occurrence in the middle to late of this century (90% to 99% probability).…”
Section: Introductionmentioning
confidence: 99%